Understandings of creative practice and pedagogy by teacher education communities in West Bank, Palestine, and North West England. Issue 3 (4th May 2021) - Adams, Jeff; Al-Yamani, Hala; Arya-Manesh, Emma; Mizel, Omar; Owens, Allan; Qurie, Dua'a
ABSTRACT: This paper discusses a collaborative research project that aimed to explore approaches to creative practices and pedagogies by teacher education communities in the West Bank, Palestine, and North West England (Bethlehem and Chester). The project explored the values, attitudes and perceptions of teacher educators and student teachers in relation to creative pedagogies and the conditions under which they flourished in each community. We found that creativity was understood to take many forms, according to the cultural values and conditions present in each community, and that creative pedagogical forms emerged from the specificities of their cultural and political contexts. Creativity in education is a contentious issue in both cultures, but an area that both education communities wished to explore further. Despite the differences, there were surprising commonalities between the two communities about the value of creative practices and the relation of creativity to democratic and critical practices in the classroom.